The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.21273/hortsci.41.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Detection of Nitrogen in Chinese Cabbage Leaves Using VIS–NIR Spectroscopy

Abstract: Proper nutrient management is essential to increase yield, quality and profit. This study was conducted to estimate the N concentrations of chinese cabbage (Brassica campestris L. ssp. pekinensis `Norangbom') plug seedlings using visible and near infrared spectroscopy for nondestructive N detection. Chinese cabbage seeds were sown and raised in three 200-cell plug trays filled with growing mixture in a plant growth chamber with three different level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 14 publications
6
20
0
Order By: Relevance
“…Figure 2b shows the average spectral reflectance curves of different dates. The wavelength at 555 nm is the nitrogen absorption band which correlates to absorbed light by nitrogen within the crop tissue [27] . It shows that spectral reflectance values at 555 nm generally increased with time.…”
Section: Spectral Featuresmentioning
confidence: 99%
“…Figure 2b shows the average spectral reflectance curves of different dates. The wavelength at 555 nm is the nitrogen absorption band which correlates to absorbed light by nitrogen within the crop tissue [27] . It shows that spectral reflectance values at 555 nm generally increased with time.…”
Section: Spectral Featuresmentioning
confidence: 99%
“…It probably influences the accuracy of model for the prediction of FLAV and NBI. Correlational study was found by Min et al (2006), who stressed that the regions of 1910 and 1938 nm highly related to water might have a strong impact on the N concentration prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al developed a handhold spectral instrument to diagnose the growth status of the crop in greenhouse using optical fibers [5] . Min et al investigated the use of a visible and NIR spectroscopy to estimate nitrogen concentration of Chinese cabbage [12] . Xu, Z. et al developed an optical sensor after analyzing the optical characters of spectral reflectance of canopy and the optical principle of non-destructive nitrogen monitoring [13] .…”
Section: Research Backgroundmentioning
confidence: 99%